menu
QAmmunity.org
Login
Register
My account
Edit my Profile
Private messages
My favorites
Register
Ask a Question
Questions
Unanswered
Tags
Categories
Ask a Question
If f(x)=3x-2 and g(x)=(1)/(3)x+1, then (f(g))^(-1) (x) equals: a. 1-x b. x-1 c. (1)/(3) (3x-1) d. x+1
asked
Jun 13, 2023
169k
views
1
vote
If
and
, then
equals:
a.
b.
c.
d.
Mathematics
college
Evan Shaw
asked
by
Evan Shaw
4.7k
points
answer
comment
share this
share
0 Comments
Please
log in
or
register
to add a comment.
Please
log in
or
register
to answer this question.
1
Answer
3
votes
Answer:
B) x - 1
=================
Given
f(x) = 3x - 2, g(x) = 1/3x + 1
Find the composite function f(g(x))
f(g(x)) = 3(1/3x +1) - 2 = x + 3 - 2 = x + 1
Find the inverse of f(g(x))
x = f(g)⁻¹(x) + 1
f(g)⁻¹(x) = x - 1
Correct
choice
is
B
Irlanda
answered
Jun 18, 2023
by
Irlanda
4.7k
points
ask related question
comment
share this
0 Comments
Please
log in
or
register
to add a comment.
Ask a Question
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.
5.2m
questions
6.7m
answers
Other Questions
Pizza planet is running a special 3 pizzas for 16.50. What is the unit rate for one pizza
What number is halfway between 0 and 18
If the 9-inch wheel of cheese costs $18.60, what is the cost per square inch? If the cost is less than a dollar, put a zero to the left of the decimal point?
Need answer to math problem!!!
Which property is shown in the problem below? -8(x-3y-9) = -8x+24y+72 A the associative property B the commutative property C the distributive property D the division property ASAP
Twitter
WhatsApp
Facebook
Reddit
LinkedIn
Email
Link Copied!
Copy
Search QAmmunity.org